2011
DOI: 10.1680/stbu.2011.164.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Wind-induced vibrations of buildings: role of transient events

Abstract: The design of tall buildings, in many cases, is governed by habitability limit states, where accelerations predicted from wind tunnel studies emulating stationary, boundary layer flows associated with synoptic winds are compared to accepted standards for occupant comfort. In both the accelerations predicted for these design limit states and the criteria they are evaluated against, tall building design practice has consciously neglected other types of responses that result from more transient wind events, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Another point discussed in this article is that superimposition of transient, dynamic wind effects on semi-static (quasi-steady state) wind effects is a problem known since long [ 30 ], but its significance was recently only realized even for tall buildings [ 31 ]. In this study, impacts of such superimposition are examined for a small structure.…”
Section: Discussionmentioning
confidence: 99%
“…Another point discussed in this article is that superimposition of transient, dynamic wind effects on semi-static (quasi-steady state) wind effects is a problem known since long [ 30 ], but its significance was recently only realized even for tall buildings [ 31 ]. In this study, impacts of such superimposition are examined for a small structure.…”
Section: Discussionmentioning
confidence: 99%
“…The T K Hsieh Award, presented annually to the authors of the best paper published by the Institution in the field of structural and soil vibration, was awarded to Kijewski-Correa and Bentz (2011).…”
Section: T K Hsieh Awardmentioning
confidence: 99%
“…Based on the approach, Kijewski‐Correa and Pirnia 17 studied the effects of coupling, beat phenomenon, amplitude dependence, and structural system type on dynamic properties, as well as correlating observed periods of vibration against finite element predictions. Besides, they also analyzed the dynamic properties of a 245.7 m high building in Boston, 16 a 264 m high building 16–18 in Seoul, and four tall buildings 19 in Chicago under wind load. Quan et al 20 identified the natural frequencies and damping ratios of the Shanghai World Financial Center based on the measured data by using HHT and RDT.…”
Section: Introductionmentioning
confidence: 99%